Putting a Price on Culture: Ethnic Organisations, Volunteers, and the Marketing of Multicultural Festivals - Thoroski, Cynthia; Greenhill, Pauline (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2001)
The literature from anthropology and from other disciplines which have approached tourism and cultural tourism suggests a perennial problem; these practices tend to destroy their own object. This danger is particularly acute where tourism relies upon experiences of “unspoiled” nature or “non-Westernised” culture. Tourists often degrade or even destroy the environment they are there to appreciate, and their expectations for exotic cultural experiences fail to take into consideration the lived realities of the peoples they have commodified. Folklorama, along with other ethnic festivals, is subject to similar pressures. The authors’ focus upon Folklorama gives them an in-depth perspective upon the individuals and groups who participate, more than upon hierarchies, infrastructures, and governing bodies.